Supplementation of ammoniated wheat straw in wintering diets of gestating beef cows - T.J. Beck; D.D. Simms; Robert T. Brandt Jr.; R.C. Cochran; Gerry L. Kuhl (Kansas Agricultural Experiment Station Research Reports, 1991)
During two winters, 96 beef cows in late gestation were utilized in 60-day precalving feeding trials to evaluate supplementation for cows fed ammoniated wheat straw. Treatments included: control--mineral supplement only (C), 3 lbs milo + mineral (3M), 6 lb milo + mineral (6M), and 2.75 lb milo + .75 lb soybean meal + mineral (SBM). 3M increased (P<.05) cow gain over control but body condition changes were similar. 6M and SBM resulted in similar gains and body weight changes, which were higher than those of cows receiving either C or 3M. Birth weight of calves, percent cycling at the start of breeding, and percent pregnant after a 60-day breeding season were not affected by treatment. Natural protein appears to be a major limiting nutrient in cows fed ammoniated wheat straw.
Keywords: Cattlemen' s Day; 1991; Kansas Agricultural Experiment Station contribution; no. 91-355-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 623; Beef; Ammoniation; Wheat straw; Cows; Supplementation